Can Social Protection Really Make a Significant Contribution to Poverty Reduction? The Case of Romania - Mihaela Ifrim (CES Working Papers, 2014)
Most Romanians believe that the state should assume more responsibility for the welfare of everyone. Social protection must actually be understood in the broader framework of gradual and more alert transfer of the responsibility from the individual to the state level. If in the case of a minimal state the individuals would be forced to save to cope with unforeseen situations like job loss, disability or illness, in the case of a welfare state, which guarantees minimum incomes, these reasons fade. Individuals have increasing expectations from the authorities, and largely decline their capabilities of helping others through charity or philanthropy. In the light of the lack of confidence in the strength of private actions to support those in need, public solutions are expected to eliminate poverty through social protection programs. The purpose of this paper is to analyze the ability of social protection programs in Romania to help improve well-being among the most disadvantaged citizens of Romania and the costs associated with such objective.
Keywords: E64; I32; 330; social protection; minimum guaranteed income; poverty; Romania Romania